Examining positional difference in basketball players` field goal accuracy using Bayesian hierarchical model - Wang, F.; Zheng, G. (International Journal of Sports Science & Coaching, 2022)
This study developed a Bayesian Hierarchical Modeling Scheme to study the positional difference of field goal accuracy at different shooting distances, including less than 8 ft, 8-24 ft, and more than 24 ft. The approach was first applied to players` statistics in the National Basketball Association (NBA) 2018-2019 season in the USA. Results found that the overall accuracy decreases with the increase in shooting distance. When the shooting distance is less than 8 feet, players in the role of center have the highest accuracy (63.2%). The point guard and shooting guard have higher shooting accuracy than power forward and small forward. When the shooting distance is between 8 and 24 feet, the guards, including the shooting guard and point guard, have the highest shooting accuracy. For the 3-point field goal with a shooting distance of more than 24 feet, the point guard and shooting guard have the highest shooting accuracy, with a mode of 0.362, respectively. To further demonstrate the use of the proposed method, shooting accuracy at different distances was investigated for NBA basketball seasons in the last decade (2011-2020). Analyzes found that shooting accuracy for distinct positions at different shooting distances is generally higher in the last five years (from 2016-2017 season to 2020-2021 season) compared to the first five years (from 2011-2012 season to 2015-2016 season). Increases in the accuracy of field goals with shooting distance over 24 feet have been observed for players who take the roles of center, power forward, and shooting guard.